Positional variation of AA5083-H112 and AA6061-T6 alloys: Modified friction stir clinching. (February 2022) - Fan, Guangli; Xue, Chengfeng; Ojo, Olatunji Oladimeji; Bokov, Dmitry; Mehrez, Sadok; Paidar, Moslem; Xu, Jin
Abstract: The modified friction stir clinching process was utilized to join the AA5083-H112 and AA6061-T6 aluminum alloys by examining materials positioning effect, physical features (flash properties and effective upper sheet thickness), interface microstructure, and tensile properties of the resultant joints. The AA6061-T6/AA5083-H112 weld arrangement (condition #2) produced a better pin- and shoulder cavity refilling as compared to the AA5083-H112/AA6061-T6 (condition #1) due to better visco-plastic behavior/flowability phenomenon. The percentage fractions of the effective upper sheet thicknesses are 47% (condition #1) and 39% (condition #2) respectively. Tensile results, material flow, microstructures are significantly influenced by materials positioning. Serious attention must be paid to the materials positioning to improve the weld properties of the modified friction stir clinching between AA6061-T6 and AA5083-H112 alloys. Highlights: Dissimilar modified friction stir clinching of AA5083 to AA6061 was conducted. The impact of the material positioning on the microstructure and mechanical properties was investigated. The AA6061-T6/AA5083-H112 weld arrangement (condition #2) produced a better pin-and-shoulder cavity refilling due to better visco-plastic behavior/flowability phenomenon. The AA6061-T6/AA5083-H112 weld arrangement (condition #2) produced better tensile-shear and cross-tension loads.